Engineering statistics - Montgomery, Douglas C.; Runger, George C.; Hubele, Norma Faris 1953- (John Wiley & Sons, Inc., 2012)
Montgomery, Runger, and Hubele provide modern coverage of engineering statistics, focusing on how statistical tools are integrated into the engineering problem-solving process